Comparison of the Effectiveness of Hematoma Block Versus Conscious Sedation in Close Reduction of Distal Radius Fracture (Journal of Pakistan Orthopaedic Association, 2018)
Objectives: To compare the effectiveness of hematoma block versus conscious sedation in close reduction of distal radius fracture in term of pain reductionMethods: This Randomized controlled trail was conducted in the Department of Orthopaedic Hayatabad Medical Complex Peshawar from March 2015 to February 2016. In this study a total of 76 (38 in each group) patients were observed. Hematoma block was allocated group–A and conscious sedation was allocated group-B.Results: The mean age in group A was 42.05 (SD ± 12.08) years. While the mean age in group B was 47 (SD ± 11.61) years. In group A, male patients were 11 (28%) while female were 27(72%). Male patients were in group B 12(32%) while female was 26(68%). Effectiveness in group A was 26(68%) while (12)32% was non-effective. Effectiveness in group in group B was 11(28%) while 27(72%) was non-effective.Conclusion: Our study show that hematoma block is more effective than conscious sedation in close reduction of distal radius fracture in term of pain reduction.